ANALYSING THE INCIDENCE OF COMPLICATIONS ASSOCIATED WITH KNEE ARTHROSCOPY - AHMED , J; GHAFFAR , A; FAROOQUE , MU; KIFAYATULLAH, MR; HUSSAIN , S; ANWAR , K (Biological and Clinical Sciences Research Journal, 2024)
Knee arthroscopy is a minimally invasive surgical technique for diagnosing and treating knee conditions. While generally safe, complications can occur, ranging from minor infections to severe nerve damage or septic arthritis. Understanding these complications is essential for optimal patient care. Objective: To explore the occurrence of complications related to knee arthroscopy. Methods: After the ethical approval from the institutional review board, this retrospective cohort study was conducted at JPMC Karachi from 01/09/23 to 29/02/24. Through the non-probability consecutive sampling, patients between ages 18 and 50, either gender and patients undergoing elective arthroscopy procedures were included in the present study. Detailed documentation of difficulties during surgery and recovery, such as infections, blood clots, nerve damage, and mechanical issues, is crucial for assessing the frequency and seriousness of negative outcomes. Results: Synovectomy (79%) followed by Meniscectomy 78% was the common arthroscopic procedure performed. The incidence of complications after the arthroscopic procedure in the present study was 23%. Septic arthritis (33%), followed by Neural, vascular, or ligament injury and superficial infections (20%) were the complications observed in the present study. Conclusion: Arthroscopic knee surgeries are minimally invasive, generally safe procedures with low complication rates. Within this series were 15 (2%) complications, with five occurrences (33%) explicitly involving septic arthritis.